Synthesis of irregular sets of fre quencies for synchronization of processes in automation - V.A. Ivanov; A.E. Boyarchuk; A.G. Karpika (Advanced Engineering Research, 2009)
The new decision of a task of synthesis of set of frequencies for the purposes of synchronization of processes in automation is offered. The difference from now in use «grid» of set of frequencies with a constant step is, that the formation of set of grids or set of irregular meanings of frequencies is provided. It is achieved by the shown opportunity of representation of the initial data by fractional numbers with the variable basis of a fractional part. Opportunities of means of synchronization on accuracy and nomenclature of frequencies thus extend.